Type II band alignment in InAs zinc-blende/wurtzite heterostructured nanowires. (6th September 2016) - Panda, Jaya Kumar; Chakraborty, Arup; Ercolani, Daniele; Gemmi, Mauro; Sorba, Lucia; Roy, Anushree
Abstract: In this article we demonstrate type-II band alignment at the wurtzite/zinc-blende hetero-interface in InAs polytype nanowires using resonance Raman measurements. Nanowires were grown with an optimum ratio of the above mentioned phases, so that in the electronic band alignment of such NWs the effect of the difference in the crystal structure dominates over other perturbing effects (e.g. interfacial strain, confinement of charge carriers and band bending due to space charge). Experimental results are compared with the band alignment obtained from density functional theory calculations. In resonance Raman measurements, the excitation energies in the visible range probe the band alignment formed by the E 1 gap of wurtzite and zinc-blende phases. However, we expect our claim to be valid also for band alignment near the fundamental gap at the heterointerface.